Unlocking the Green Growth Puzzle: Exploring the Nexus of Renewable Energy, CO2 Emissions, and Economic Prosperity in G7 Countries - Gafsi, Nesrine; Bakari, Sayef (International Journal of Energy Economics and Policy, 2025)
The primary aim of this research endeavor is to elucidate the intricate dynamics among renewable energy utilization, CO2 emissions, and the trajectory of economic growth within the framework of G7 Countries over the extensive timeframe from 1997 to 2021. Through the meticulous application of cointegration analysis and the Panel Vector Error Correction Model, our empirical investigation unveils a substantiated positive impact of the utilization of renewable energy sources and CO2 emissions on economic growth trends in the long term. Nevertheless, our comprehensive analysis suggests a notable absence of any observable relationship between renewable energy adoption, CO2 emissions, and short-term economic growth dynamics. In light of our findings, it is recommended that policymakers focus on fostering sustainable long-term strategies for renewable energy adoption and CO2 emissions reduction, while also acknowledging the limited short-term impact on economic growth dynamics.